2021
DOI: 10.1007/s11468-021-01514-6
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Spectroscopic and Theoretical Analysis of Plasmonic Silver Nanoparticle Sensor Towards Detailed Microscopic Understanding of Heavy Metal Detection

Abstract: Plasmonic nanoparticles are of great importance owing to their highly responsive 'Localized Surface Plasmon Resonance' (LSPR) behaviour to self-agglomeration/ aggregation leading to the development of various nanosensors. Herein we demonstrated the definite self-assembly of citrate functionalized silver nanoparticles (AgNPs) into a one-dimensional linear chain in presence of charged lead ions (Pb 2+ ), one of the most toxic heavy metal pollutants. We have explored detail mechanism using a variety of spectrosco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…These DRS results imply that AgNPs formed similar chain-like aggregates even on RPPs, so we obtained the transverse and longitudinal modes of vibration corresponding to the formed chain aggregates. Also, it is evident from the DRS that there was a gradual red shift in the second (520 nm) peak with a simultaneous decrease in the first peak (395 nm), which confirmed the formation of longer chain aggregates 30 with an increment in the Pb extract concentration. The formation of longer chain aggregates with the increase in the Pb concentration is also the cause of the increase in the red content (visually) of the RPPs.…”
Section: Properties and Sensing Mechanism On The Developed Paper Subs...mentioning
confidence: 64%
See 4 more Smart Citations
“…These DRS results imply that AgNPs formed similar chain-like aggregates even on RPPs, so we obtained the transverse and longitudinal modes of vibration corresponding to the formed chain aggregates. Also, it is evident from the DRS that there was a gradual red shift in the second (520 nm) peak with a simultaneous decrease in the first peak (395 nm), which confirmed the formation of longer chain aggregates 30 with an increment in the Pb extract concentration. The formation of longer chain aggregates with the increase in the Pb concentration is also the cause of the increase in the red content (visually) of the RPPs.…”
Section: Properties and Sensing Mechanism On The Developed Paper Subs...mentioning
confidence: 64%
“…, the average diameter is 8 nm. 30 We found that a 50 μL volume of sample, which includes 30 μL of Pb extract and 20 μL of the AgNPs sensor, is needed for the best colorimetric response. We analyzed the effects of pH, temperature and time dependence on the performance of the sensor.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations